Induced pluripotent stem cell-derived and directly reprogrammed neurons to study neurodegenerative diseases: The impact of aging signatures - Aversano, Simona; Caiazza, Carmen; Caiazzo, Massimiliano (Frontiers in Aging Neuroscience, 2022)
Several diseases of the central nervous system are age-associated and do not directly result from genetic mutations. These include late-onset neurodegenerative diseases (NDDs), which represent a challenge for biomedical research and drug development, due to the impossibility to access to viable human brain specimens. Advancements in reprogramming technologies have allowed to obtain neurons from induced pluripotent stem cells (iPSCs) or directly from somatic cells (iNs), leading to the generation of better models to understand the molecular mechanisms and design of new drugs. Nevertheless, iPSCs technology faces some limitations due to reprogramming-associated cellular rejuvenation which resets the aging hallmarks of donor cells. Given the prominent role of aging for the development and manifestation of late-onset NDDs, this suggests that this approach isn’t the most suitable to accurately model age-related diseases. Direct neuronal reprogramming, by which a neuron is formed via direct conversion from a somatic cell without going through a pluripotent intermediate stage, allows the possibility to generate patient-derived neurons that maintain aging and epigenetic signatures of the donor. This aspect may be advantageous for investigating the role of aging in neurodegeneration and for finely dissecting underlying pathological mechanisms. Here, we will compare iPSCs and iNs models as regards the aging status and explore how this difference is reported to affect the phenotype of NDD in vitro models.